2022
DOI: 10.3390/ijerph19053024
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Distribution and Identification of Ticks on Livestock in Pakistan

Abstract: Background: Ticks are ectoparasites that transmit a variety of pathogens that cause many diseases in livestock which can result in skin damage, weight loss, anemia, reduced production of meat and milk, and mortality. Aim: The aim of this study was to identify tick species and the distribution on livestock hosts (sheep, goat, dairy cattle, and buffalo) of Punjab, Khyber Pakhtunkhwa Province and Islamabad from October 2019 to November 2020. Materials and Methods: Surveillance was performed to calculate the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
3
7
1
Order By: Relevance
“…The present study showed a statistically significant difference ( P < .05) in the prevalence of tick infestation between females and males. This finding was in agreement with reports from Pakistan 31,32 and Colombia, 33 reported that female cattle had a significantly higher tick burden than males. However, the finding disagree with another study, which reported a higher tick infestation in male than females animals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study showed a statistically significant difference ( P < .05) in the prevalence of tick infestation between females and males. This finding was in agreement with reports from Pakistan 31,32 and Colombia, 33 reported that female cattle had a significantly higher tick burden than males. However, the finding disagree with another study, which reported a higher tick infestation in male than females animals.…”
Section: Discussionsupporting
confidence: 93%
“…It was also suggested that the grooming of calves and the smaller surface area of animals may be factors in the lower tick burdens. 32 There was no significant difference between the body condition score in this study and previous observations in the same area. 19 A significantly higher prevalence was observed in poorbody-conditioned animals than in medium-and good-bodyconditioned animals.…”
Section: Environmental Health Insightscontrasting
confidence: 70%
See 1 more Smart Citation
“…A similar study in 2 districts of lower Punjab in zone 3 reported Hyalomma as the predominant genus, followed by Rhipicephalus (39). In Multan, sheep and goats showed the prevalence of Hyalomma and Rhipicephalus infestation (40). A similar study on ticks in Quetta in zone 8 has been reported (41).…”
Section: Discussionsupporting
confidence: 71%
“…sanguineus s.l. from Pakistan [ 17 , 26 , 67 ], to date no molecular evidence has been provided to solve and confirm the status of the actual species and its lineage from Pakistan. Molecularly, earlier works have revealed that a minimum of three distinguished mitochondrial lineages of Rh.…”
Section: Discussionmentioning
confidence: 99%